The Determinants of Saving Behavior in Students: The Role of Self-Control as a Mediating Variable: Determinants of Saving Behavior in Students: The Role of Self-Control as a Mediating Variable - Azizah, Ayu Nur; Meiriyanti, Rita; Amelia, Dhea Rizky (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The low level of student savings is the reason why the purpose of this study is to analyze and find out the influence between financial literacy, financial inclusion and individual modernity on saving behavior both directly and mediated by self-control. This study uses quantitative methods and data collection techniques by distributing questionnaires through google forms. The population in this study is the Faculty of Economics and Business, University of PGRI Semarang with a sample of 314. The data analysis technique uses Structural Equation Modeling (SEM) through the SmartPLS 3.0 application. The results of this study show that financial literacy, financial inclusion and individual modernity have a direct effect on saving behavior and self-control has a role as a mediator between financial literacy, financial inclusion and individual modernity on students’ saving behavior.